Finite Element Analysis of Spline-Connecting Anti-roll Torsion Bar Based on ABAQUS - 王京雁; 卜继玲; 曾晶晶; 刘柏兵; 黄友剑 (机车电传动)
A spline-connecting anti-roll torsion bar was simulated by ABAQUS software, which was shown being correct and reliable by comparing the results with the experiment. With using of sub-model, the local stress distribution of the spline was obtained.The results indicated that simplifying the contact relation of the entirety model could reduce the computational cost and increase analysis efficiency, and the sub-model solution solved the problems of too much grid need to calculate, long calculate time and the poor convergence. The accurate stress results provided strong support for the fatigue analysis and the extraction of the fatigue failure mode of the torsion bar system.